Spatial Analysis of Health Facility Locations and Tuberculosis Treatment Outcomes in Jambi City, 2024 - Suhermanto; Fakhrida Khairat; Erwin Hari Astuti; Naris Dyah Prasetyawati (Gema Lingkungan Kesehatan, 2025)
Tuberculosis (TB) remains a global health problem with an increasing incidence rate, including in Indonesia. Jambi City has experienced an increase in TB cases from year to year, while the treatment success rate has not reached the target. This study aimed to analyse the relationship between the location of health facilities (puskesmas), travel time, and transportation costs with TB treatment success in Jambi City. This study was an observational survey with a cross-sectional design, using QGIS Overlay spatial analysis (network analysis) and Chi-Square statistical test. The sample consisted of 120 bacteriologically confirmed TB patients at four health centres. QGIS analysis showed that 98.33% of TB patients were located within the 3,000-metre service radius of the puskesmas. However, not all patients with successful treatment rated the location of the health centre as easily accessible, while a small proportion of patients with treatment failure rated the location of the health centre as difficult to access. Chi-Square test results showed no significant association between the location of the health centre and TB treatment success (p = 0.066). Thus, the affordability of health facilities based on travel time and transport costs is not a major factor that causes non-achievement of TB treatment success targets in Jambi City. This study recommends further research to identify other factors that may influence TB treatment success, such as patient compliance and quality of health services.